Characterization of an airborne organic contaminant sensor based on microfibers with sol–gel film - Miao, Xinxiang; Zhou, Guorui; Chen, Jiaxuan; Zhu, Qihua; Li, Yuhai; Jiang, Xiaodong; Lv, Haibing; Yao, Caizhen; Jiang, Yilan; Niu, Longfei; Xiang, Siheng (Frontiers in Physics, 2023)
Based on microfibers with sol-gel film, this study focuses on developing an organic contaminant sensing device to monitor airborne organic contamination in highpower laser facilities. The device heightened the sensitivity to the external environment with the nano-structure of sol-gel on the microfiber surface. The study explored the adsorption mechanism of sol-gel film to airborne organic contaminants at different concentrations. The relationship between the additional laser transmission power loss caused by contaminants and the filling rate of the porosity of the film was discussed.Besides, we obtained the relationship between the additional loss and the refractive index of the microstructure. The experimental results indicated that employing microfiber with microstructure coating could improve sensing sensitivity to airborne organic contaminants significantly. The precision of sensing surface contaminants can reach ng/cm2. When the concentration of organic contaminants is lower than 7.5%, the adsorption process of the microstructure coating is dominated by single molecule adsorption, and the additional loss increases exponentially with growing concentration, while the sensing limit is 70 ppm. When the concentration of organic contaminants exceeds 7.5%, the adsorption process of the surface microstructure coating is dominated by the multi-molecular adsorption. Therefore, the additional loss is exponentially related to the concentration of airborne organic contaminants, while the sensing limit is 10 ppm. Besides, the Langmuir monolayer adsorption isotherm model and the Freundlich multi-molecular layer adsorption isotherm model were adopted to analyze and verify the experimental results, which suggested that the experimental results agree with the simulation results well. This work can be considered for in-situ monitoring of airborne concentration contaminants and the transmittance of optics with sol-gel film, and it also provides a new research method for in-situ monitoring of airborne organic contaminants in the vacuum environment.